Peran Dukungan Sosial terhadap Parenting Self-Efficacy Ibu Bekerja dengan Anak Usia Dini - Moelyono, Cindy Amelia; Sumargi, Agnes Maria (Psychopreneur Journal, 2025)
Working mothers of young children face a constant challenge. Their limited time can impact their ability to parent effectively, while young children still require support in managing emotions and behavior. This situation can lead to a decrease in parenting self-efficacy. This study aimed to examine one of the factors that influence parenting self-efficacy, namely social support. Participants were 124 full-time working mothers, aged 20-30 years, with a first child aged 2-6 years, and living in East Java. The mothers completed online parenting self-efficacy and social support questionnaire. A regression analysis revealed a significant influence of social support on parenting-self efficacy with an effective contribution of 26.3%. Support from family, friends, and significant others all play a role in increasing parenting self-efficacy of working mothers with young children.